The Wright Brothers A Life Story - Joseph, Mary (Sterling Group, 2012)
Meet the Wright Brothers -- inventors of the airplane. The story of how they created one of the most influential machines in history is told in level-appropriate language and detailed illustrations. A Level 3 first reader.
Keywords: Autobiography & Biographies( Nigeria); Memoirs; Non Fiction